2015
DOI: 10.1097/jsm.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Total Shoulder Arthroplasty on Golfing Activity

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 5 publications
0
48
0
1
Order By: Relevance
“…There are several limitations to this study: although our sample size was larger than several previously published reports, 1,9,12,13,18 a larger study group and increased statistical power may have been able to detect a significant improvement in postoperative handicap. In addition, a larger group may have been able to better detect an association between the change in handicap and the follow-up period, surgical laterality or the implant used.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There are several limitations to this study: although our sample size was larger than several previously published reports, 1,9,12,13,18 a larger study group and increased statistical power may have been able to detect a significant improvement in postoperative handicap. In addition, a larger group may have been able to better detect an association between the change in handicap and the follow-up period, surgical laterality or the implant used.…”
Section: Discussionmentioning
confidence: 82%
“…1 There are several studies in the total hip and total knee arthroplasty literature that have assessed the effect of total joint arthroplasty on golf participation, driving distance, and handicap. 1,6,12,13,17,28 The effect of total joint arthroplasty on postoperative handicap has been mixed, with some authors reporting a decrease in postoperative handicap 1,6,9,18 and others finding the postoperative handicap to increase. 1,12,13 We sought to determine the impact of TAA on postoperative golf handicap.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the procedure was eccentric shoulder osteoarthritis in 61% of cases and revision replacement in 31% of cases. In total, 79.2% of patients resumed sports, but this rate varied depending McCarty et al 17 Schumann et al 24 Bulhoff et al 3 Papaliodis et al 22 Simovitch et al 25 Barnes et al 1 Garcia et al 6 Garcia on the type of activity. None of the patients resumed tennis.…”
Section: Included Studiesmentioning
confidence: 99%
“…Three studies evaluated the results after TSA only. 3,22,24 Papaliodis et al 22 reported that 31 of 35 golfers were able to return to sport after a mean of 8.8 months. Thirty patients experienced a significant postoperative decrease in pain.…”
Section: /A N/a N/a N/a N/a N/a N/a N/a N/a Contemporary Group N/a N/mentioning
confidence: 99%
“…Eine Befragung von 367 Patienten im Mittel 3,2 Jahre nach anatomischer TEP-Implantation hat ergeben, dass 8 Monate post-OP die Rückkehr zum Golfsport mit signifikant weniger Schmerz, verbesserter Schlagweite und reduziertem Handicap verbunden ist [73].…”
Section: Schulterendoprothetik: Spezielle Sportartenunclassified